IMPLEMENTATION OF GREEN HUMAN RESOURCE MANAGEMENT IN SMES: CHALLENGES AND OPPORTUNITIES TO ENHANCE BUSINESS SUSTAINABILITY - Permata Sari, Rr. Indah; Putra, Briyan Cadalora; Lakshita, Dhuihitta Mahardhika; Fauziah, Dien Ajeng; Sa’adah, Ummi (Yayasan Nuraini Ibrahim Mandiri, 2024)
This research examines the implementation of Green Human Resource Management (GHRM) in the context of Small and Medium Enterprises (SMEs), focusing on the challenges and opportunities faced in improving business sustainability.GHRM, which includes HR policies and practices that support environmental sustainability goals, has great potential to improve the operational efficiency and competitiveness of SMEs.However, many SMEs face barriers such as limited resources, lack of understanding of sustainability, and resistance to change. This study employs a qualitative approach, utilizing case studies of SMEs that have adopted or are planning to implement GHRM.The findings indicate that, despite persistent challenges, significant opportunities exist for enhancing business sustainability, efficiency, and corporate image through GHRM implementation. GHRM practices are anticipated to contribute to cost reduction, talent attraction, and adherence to increasingly stringent environmental regulations.This research offers recommendations for SMEs to integrate sustainability policies into HR management, thereby fortifying long-term sustainability.